LEXICAL-SEMANTIC STUDY OF METONYMS IN ENGLISH AND UZBEK LANGUAGES - Yusupov Muhammadsodiq Rizomat o'g'li, (TADQIQOTLAR, 2025)
Abstract: Metonymy, as a figure of speech and a semantic mechanism, plays a pivotal role in language, allowing speakers to express concepts through part-whole, cause-effect, or contiguity relationships. This article investigates the lexical-semantic characteristics  of  metonyms  in  English  and  Uzbek  languages,  emphasizing  their structural,  semantic,  and  functional  properties.  Using  descriptive,  contrastive,  and analytical methods, the study examines authentic texts, dictionaries, and corpora to identify patterns of metonymic expression and explore language-specific realizations. The research reveals that both English and Uzbek employ metonymy extensively in various  domains,  including  daily  communication,  literature,  and  professional discourse. English metonyms often rely on conventionalized idiomatic expressions and lexicalized forms (the crown to refer to monarchy, Hollywood for the film industry), whereas  Uzbek  utilizes  morphologically  and  syntactically  explicit  structures,  often drawing  on  culturally  salient  imagery  (to‘qimachi  markazi  –  “center  of  textile production” to denote the textile industry). The study also highlights how metonymic relations contribute to cognitive economy, textual cohesion, and expressive richness. Comparative  analysis  demonstrates  that  while  English  and  Uzbek  share  universal cognitive principles in establishing part-whole or associative relations, cultural and typological differences shape their linguistic realization. The findings have practical implications  for  translation,  lexicography,  and  language  teaching,  emphasizing  the importance  of  understanding  metonymy  for  accurate  interpretation,  cross-linguistic mapping, and effective communication.